2002
DOI: 10.1177/070674370200601s05
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of methylphenidate: Insights from PET imaging studies

Abstract: Methylphenidate (MPH) is the most commonly prescribed drug for the treatment of Attention-Deficit/Hyperactivity Disorder (ADHD). We have used Positron Emission Tomography (PET) to investigate the mechanism of action of MPH in the human brain. We have shown (a) that oral MPH reaches peak concentration in the brain 60–90 minutes after its administration, (b) that therapeutic doses of MPH block more than 50% of the dopamine transporters (DAT), and (c) that of the two enantiomers that compose MPH, it is d-threo-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
206
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(217 citation statements)
references
References 38 publications
9
206
0
2
Order By: Relevance
“…As mentioned above, DAT is primarily responsible for presynaptic reuptake of dopamine, and it has been shown that MPH blocks DAT and increases extracellular dopamine (Spencer et al, 2005;Swanson et al, 2007;Volkow et al, 2002Volkow et al, , 2005Volkow et al, , 2007. Although initial reports found large (up to 70%) increases in striatal DAT in ADHD (Dougherty et al, 1999; Krause ADHD and attention networks G Bush al, 2000), subsequent reports using different ligands and techniques have found lesser effect sizes, and in some cases, even lower DAT in ADHD .…”
Section: Functional Studies: Pet and Fmrimentioning
confidence: 99%
“…As mentioned above, DAT is primarily responsible for presynaptic reuptake of dopamine, and it has been shown that MPH blocks DAT and increases extracellular dopamine (Spencer et al, 2005;Swanson et al, 2007;Volkow et al, 2002Volkow et al, , 2005Volkow et al, , 2007. Although initial reports found large (up to 70%) increases in striatal DAT in ADHD (Dougherty et al, 1999; Krause ADHD and attention networks G Bush al, 2000), subsequent reports using different ligands and techniques have found lesser effect sizes, and in some cases, even lower DAT in ADHD .…”
Section: Functional Studies: Pet and Fmrimentioning
confidence: 99%
“…Stimulant medications bind to the DAT, inhibiting reuptake and increasing synaptic dopamine (Volkow et al, 2002). The DAT gene (DAT1) was initially investigated as a primary candidate gene for ADHD susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…28 In addition, the DAT1 10R has been associated with poor response to methylphenidate (MPH) in ADHD. 29,30 MPH has been shown to block the dopamine transporter in vivo, 31,32 and may therefore be more effective in those individuals who have more in vivo availability of the transporter.…”
mentioning
confidence: 99%